Synthesis and characterization of different soybean oil-based polyols with fatty alcohol and aromatic alcohol - Yang Fukai (De Gruyter, 2021)
In this article, five kinds of soybean oil-based polyols (polyol-E, polyol-P, polyol-I, polyol-B, and polyol-M) were prepared by ring-opening the epoxy groups in epoxidized soybean oil (ESO) with ethyl alcohol, 1-pentanol, isoamyl alcohol, p-tert-butylphenol, and 4-methoxyphenol in the presence of tetrafluoroboric acid as the catalyst. The SOPs were characterized by FTIR, 1H NMR, GPC, viscosity, and hydroxyl numbers. Compared with ESO, the retention time of SOPs is shortened, indicating that the molecular weight of SOPs is increased. The structure of different monomers can significantly affect the hydroxyl numbers of SOPs. Due to the large steric hindrance of isoamyl alcohol, p-hydroxyanisole, and p-tert-butylphenol, SOPs prepared by these three monomers often undergo further dehydration to ether reactions, which consumes the hydroxyl of polyols, thus forming dimers and multimers; therefore, the hydroxyl numbers are much lower than polyol-E and polyol-P. The viscosity of polyol-E and polyol-P is much lower than that of polyol-I, polyol-B, and polyol-M. A longer distance between the molecules and the smaller intermolecular force makes the SOPs dehydrate to ether again. This generates dimer or polymers and makes the viscosity of these SOPs larger, and the molecular weight greatly increases.